Radically Questioning the Principle of the Least Restrictive Alternative: A Reply to Nir Eyal; Comment on: "Nudging by Shaming, Shaming by Nudging" - Yashar Saghai (Kerman University of Medical Sciences, 2014)
In his insightful editorial, Nir Eyal explores the connections between nudging and shaming. One upshot of his argument is that we should question the principle of the least restrictive alternative in public health and health policy. In this commentary, I maintain that Eyal's argument undermines only a rather implausible version of the principle of the least restrictive alternative and I sketch two reasons for rejecting the mainstream and more plausible version of this principle.